Analysis of Financial Performance, Efficiency, and Organizational Growth of Zakat Management Organizations on Zakat Collection in Indonesia - Firdha Amaliah (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
The purpose of this study is to analyze the financial performance, efficiency and growth of zakat management organizations with independent variables such as liquidity ratios, amil funds, activity, efficiency and growth in zakat payments. The dependent variable used is the zakat institution which can be seen on the website of each zakat institution. The population of this study is all zakat institutions registered at BAZNAS for the 2016-2020 period. Sampling using purposive sampling method. The number of samples used in this study were 8 zakat institutions with a research period of 5 years. The analytical method used was panel data regression processed with Eviews version 10. This research was conducted in several ways to determine the appropriate model, namely: Interaction Test, Fixed Effect Test, Random Effect Test, Chow Test, Housman's test. The appropriate model is obtained after classical assumptions and hypothesis testing. The results showed that the ratio of liquidity, amil wealth and activity did not affect the distribution of zakat. While the efficiency ratio and growth ratio on the control variable have a positive effect on the distribution of zakat.